Small RNA Bidirectional Crosstalk During the Interaction Between Wheat and Zymoseptoria tritici - Ma, Xin; Wiedmer, Jasmin; Palma-Guerrero, Javier (Frontiers in Plant Science, 2020)
Cross-kingdom RNAi has been shown to play important roles during plant-pathogen interactions, and both plants and pathogens can use sRNAs to silence genes in each other. This bidirectional cross-kingdom RNAi was still unexplored in the wheat-Z. tritici pathosystem. Here we performed a detailed analysis of the sRNA bidirectional crosstalk between wheat and Z. tritici. Using a combination of sRNA-seq and mRNA-seq we were able to identify known and novel sRNAs and study their expression and their action on putative targets in both wheat and Z. tritici. We predicted the target genes of all the sRNAs in either wheat or Z. tritici transcriptome and used degradome analysis to validate the cleavage of these gene transcripts. We could not find any clear evidence of a cross-kingdom RNAi acting by mRNA cleavage in this pathosystem. We also found that the fungal sRNA enrichment was lower in planta than during in vitro growth, probably due to the lower expression of the only Dicer gene of the fungus during plant infection. Our results support the recent finding that Z. tritici sRNAs cannot play important roles during wheat infection. However, we also found that the fungal infection induced wheat sRNAs regulating the expression of specific wheat genes, including auxin related genes, as an immune response. These results indicate a role of sRNAs in the regulation of wheat defenses during Z. tritici infection. Our findings contribute to improve our understanding of the interactions between wheat and Z. tritici.